THE RELATIONSHIP OF OBESITY AND HYPERTENSION IN BRAZILIAN MEN (Fiep Bulletin - online, 2014)
The male group is more exposed to the risk of illness than women. Chronic degenerative diseases is a reality , and among them stands out hypertension and obesity that direct relationship . Temporal , quantitative approach , taking as the source DataSUS . The overall objective was to investigate the relationship of hypertension and obesity in men as well as identify the age and race in which these diseases occur most prevalent in the Southeast and Northeast over the period 2008-2012 . Results revealed that hypertension was more frequent in the Southeast in 2008 , an upward trend , and the Northeast in 2010 , with ascending and then descending behavior . Unlike the literature and data from Brazil , the breed most affected region in the southeast was branca.No Northeast mulatto was the most prevalent , reinforcing the literature . It is necessary to incorporate preventive measures with emphasis on physical activity and eating habits to combat obesity and controlling blood pressure , lowering their rates of complications and hospitalizations .
Keywords: Men; obesity; hypertension